Effectiveness of mono antiplatelet therapy vs dual antiplatelet therapy in ischemic stroke or transient ischemic attack—Special subgroup consideration for the African‐American Population. Issue 7 (21st April 2020) - Borghol, Amne; Onor, Ifeanyi; Neuliep, Alison; Zaki, Ahmed; Andonie, Gabriela; Zaki, Amir; Bergeron, Bree; Castro, Mikee; Beyl, Robbie; Brakta, Fatima; Hawawini, Fadi; Ahmed, Fahamina
Abstract: Purpose: The purpose of this study is to assess the effectiveness of mono antiplatelet therapy vs dual antiplatelet therapy in reducing recurrent stroke and mortality in patients with ischemic stroke or transient ischemic attack (TIA). A subgroup analysis was conducted to compare outcomes in African‐American patients compared with non–African‐American patients. Methods: This is a single‐centre, retrospective, chart review, cohort study conducted at the University Medical Center New Orleans (UMCNO), New Orleans, Louisiana. This study includes all patients who are admitted to UMCNO with a diagnosis of ischemic stroke or TIA. The subjects were divided into two groups, patients who received mono antiplatelet therapy and patients who received dual antiplatelet therapy. Results: A total of 762 stroke patients were included in the study. Of these, 499 (65.5%) received mono antiplatelet therapy and 263 (34.5%) patients received dual antiplatelet therapy. There was no statistical significant difference in the incidence of mortality and recurrent stroke in the mono antiplatelet therapy group compared with the dual antiplatelet therapy group. When comparing primary outcomes between African Americans and non–African Americans, there was no statistical significant difference in mortality rate and recurrent stroke rate between the two groups. Conclusion: This study found no statistical significant difference in the incidence of recurrent stroke and mortality between mono antiplatelet therapy and dual antiplatelet therapy among patients who had ischemic stroke or TIA; with similar findings in a subgroup analysis comparing outcomes in African‐American patients compared with non–African‐American patients.